Metal Sulphides: A General Strategy to Fabricate Carbon‐Coated 3D Porous Interconnected Metal Sulfides: Case Study of SnS/C Nanocomposite for High‐Performance Lithium and Sodium Ion Batteries (Adv. Sci. 12/2015). Issue 12 (December 2015) - Zhu, Changbao; Kopold, Peter; Li, Weihan; van Aken, Peter A.; Maier, Joachim; Yu, Yan
Abstract : A novel generalizable strategy is proposed by Y. Yu and co‐workers in article 1500200 for fabrication of a 3D porous interconnected metal sulfide/carbon nanocomposite by the electrostatic spray deposition technique. Such a technique is simple but versatile and can be easily applied to other compounds. The obtained SnS/C composite exhibits a high reversible capacity, high rate capability and long cycling stability for both lithium and sodium storage.